MiFID 2: New developments concerning conduct of business rules. Special reference to investment advice (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This article will summarize the main developments introduced by the reform proposal of the European Commission of MiFID published in October 2011 andspecifically those relating to new rules of conduct with particular reference to those relating to investment advice. It is structured in three parts. In the first of which it is carried out a quick review of the current rules already in place and how they are affected by the proposed reform of MiFID, a second part in which it is analyzed investment advice in detail and a third part that pretend to present some experiences and difficulties encountered in the implementation of regulations relatedto investment advice.
Keywords: Appropriateness and suitability tests; Directive 2004/39/EC “MIFID”; Execution only services; Financial Instruments; Inducements; Independent investment advice; Discrectionary Portfolio management; Finnancial Rules of business conduct